(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: Coronavirus disease 2019 (COVID-19) is an emerging contagious disease and also a global health concern. Globally, this pandemic has become a prodigious threat to all, particularly affecting the undergraduate students to continue their studies in Bangladesh. Objective: To assess the level of knowledge regarding quarantine and isolation of coronavirus disease among undergraduate students. Methods: This cross-sectional study was conducted from January 2020 to December 2020 among conveniently selected 194 undergraduate students from four universities in Dhaka, Bangladesh. Data were collected electronically through Google form using a semi-structured questionnaire. Results: The mean age of students was 22.77±1.93 years which ranged from 19-29 years. Three-fourths (75.3%) of students resided in urban settings and four-fifths (80.9%) came from joint families. The students had good knowledge about quarantine (79.4%) and average knowledge about isolation (51.0%). Levels of knowledge about quarantine were statistically significant with age group, residence, family type and monthly family income. Levels of knowledge about isolation were significantly associated with family type and monthly family income. Conclusion: These results may lead to good public health practices among undergraduate students and also in the community. In this situation, increasing the knowledge of undergraduate students regarding quarantine and isolation can play an important role in improving the current situation. JAFMC Bangladesh, Vol 19, No 2 (December) 2023: 37-41